2018
DOI: 10.1073/pnas.1814610115
|View full text |Cite
|
Sign up to set email alerts
|

Ta2+-mediated ammonia synthesis from N2and H2at ambient temperature

Abstract: In a full catalytic cycle, bare Ta2+ in the highly diluted gas phase is able to mediate the formation of ammonia in a Haber–Bosch-like process starting from N2 and H2 at ambient temperature. This finding is the result of extensive quantum chemical calculations supported by experiments using Fourier transform ion cyclotron resonance MS. The planar Ta2N2+, consisting of a four-membered ring of alternating Ta and N atoms, proved to be a key intermediate. It is formed in a highly exothermic process either by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 138 publications
6
42
0
1
Order By: Relevance
“…Bader charge analysis was also carried out to demonstrate the charge transfer (CT) between metal and ligand (Table ). In the DAC case, the metal ligand charge transfer was around TM2+, which is similar to the previous report of Ta2+ . But in the SAC case, IIIB series elements showed slightly stronger CT than IVB series counterparts, and they were almost TM 2 + , except for the magnetic case of Mn anchored system.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Bader charge analysis was also carried out to demonstrate the charge transfer (CT) between metal and ligand (Table ). In the DAC case, the metal ligand charge transfer was around TM2+, which is similar to the previous report of Ta2+ . But in the SAC case, IIIB series elements showed slightly stronger CT than IVB series counterparts, and they were almost TM 2 + , except for the magnetic case of Mn anchored system.…”
Section: Resultssupporting
confidence: 87%
“…In the DAC case, the metal ligand charge transfer was around TM + 2 , which is similar to the previous report of Ta + 2 . 46 But in the SAC case, IIIB series elements showed slightly stronger CT than IVB series counterparts, T A B L E 1 Geometric and the other parameters of the SAC and DAC: coordination number (CN), metal-N (d TM-N ) and metal-metal bond length (d TM ) and the average metal ligand charge transfer (MLCT) between the metal and substrate C 2 N, overpotential of NRR (η) and potential limiting step (PLS) Mn Sc Y La Ti Zr Hf TM NC 3 3 2 2 2 6 2 F I G U R E 5 N 2 molecule activation mechanism for the DAC, A, and SAC, B and C. The π (left) and σ (right) splitting of LOL for N 2 adsorption on the double anchored V, D, single anchored Sc, E, and Ti, F, respectively and they were almost TM 2+ , except for the magnetic case of Mn anchored system. The occupation of the split d orbital was the main difference in both SAC and DAC systems.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, metal clusters that bring about scission of the N≡N bond have served as prototypical systems to probe the active sites in heterogeneous catalysis (9,20,21). Indeed, recent combined experimental/ theoretical gas-phase studies provided a conceptual understanding of dinitrogen activation and conversion (22)(23)(24)(25).…”
mentioning
confidence: 99%
“…However, examples of structurally well-defined complexes rendering a complete cleavage of the N≡N triple bond are rather limited so far (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Experiments using matrix isolation have shown that dimers of transition metals can split completely the triple bond of N 2 and form M 2 N 2 molecules consisting of a 4-membered, mostly planar ring; in the latter, the 2 nitrogen atoms are connected to both metal atoms but no longer to each other (30).…”
mentioning
confidence: 99%
“…Banyak senyawa yang paling penting pada bidang industry, seperti amonia (42)(43)(44)(45)(46) , asam nitrat (47) , nitrat organik (propelan dan bahan peledak), serta sianida, mengandung nitrogen. Nitrogen banyak ditemukan dalam bentuk ikatan rangkap dua dan tiga, namun ada juga yang membentuk ikatan tunggal(single bond) (48)(49)(50)(51)(52)(53) .…”
Section: Karakter Atom Penyusun Dari Senyawa Nh4cl 51 Nitrogen N Gamunclassified